1993
DOI: 10.1007/bf02374491
|View full text |Cite
|
Sign up to set email alerts
|

Is microalbuminuria part of the prediabetic state? The Mexico City Diabetes Study

Abstract: Microalbuminuria is associated with increased cardiovascular mortality in both diabetic and non-diabetic subjects. A number of studies have indicated that insulin resistance, increased blood pressure and dyslipidaemia precede the onset of clinical diabetes. We examined various correlates of microalbuminuria in 1,298 non-diabetic subjects who participated in the Mexico City Diabetes Study, a population-based study of diabetes and cardiovascular risk factors. Both parental history of diabetes and impaired glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
56
1
3

Year Published

1995
1995
2003
2003

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 45 publications
8
56
1
3
Order By: Relevance
“…Dysfunction of these cells may increase intraglomerular pressure and/or decrease glomerular charge and size selectivity and thus cause microalbuminuria. Alternatively, hyperhomocysteinemia and (micro)albuminuria could be associated through a common pathophysiological pathway; eg, inadequate vitamin B 6 , B 12 , and/or folate status could be the common antecedent leading to hyperhomocysteinemia on the one hand and to the development of (micro)albuminuria on the other. However, there is no evidence that inadequate B-vitamin status can directly cause (micro)albuminuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysfunction of these cells may increase intraglomerular pressure and/or decrease glomerular charge and size selectivity and thus cause microalbuminuria. Alternatively, hyperhomocysteinemia and (micro)albuminuria could be associated through a common pathophysiological pathway; eg, inadequate vitamin B 6 , B 12 , and/or folate status could be the common antecedent leading to hyperhomocysteinemia on the one hand and to the development of (micro)albuminuria on the other. However, there is no evidence that inadequate B-vitamin status can directly cause (micro)albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…Microalbuminuria has been proposed to be part of the insulin resistance syndrome, 12,13 but not all studies concur. 20,34,35 Previous prospective studies 4 have not demonstrated a high insulin level or insulin resistance to be associated with an increased risk of developing microalbuminuria, which is in accordance with the present data.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the ®ndings of microalbuminuria in newly diagnosed NIDDM and impaired glucose tolerance, Haffner 16 proposed that microalbuminuria in nondiabetic subjects represents part of a pre-diabetic state. In the current study, participants with diabetes mellitus and impaired glucose tolerance were excluded, yet 2 h post 75 g Polycose load plasma glucose concentrations were weakly associated with degree of albuminuria in all participants as a group (Table 6), but did not reach statistical signi®cance in each ethnic group.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate comparisons, we roughly approximate the conventional boundaries of microalbuminuria (20 Use of semi-quantitative tests, which tend to overestimate urine albumin concentration, 7,8 may, to some extent, explain the unusually high prevalence of microalbuminuria reported in some large-scale studies. [9][10][11][12] Urine albumin concentrations measured in 'spot' morning collections are frequently standardised for concurrent creatinine excretion to derive ACRs. This procedure corrects for unknown urine volumes but needs differentiation of males from females in whom creatininuria is lower because of reduced muscle mass, a fact not always taken into account.…”
Section: Populations At Largementioning
confidence: 99%